1996
DOI: 10.1111/j.1365-3040.1996.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative growth rate correlates negatively with pathogen resistance in radish: the role of plant chemistry

Abstract: Plant growth rate has frequently been associated with herbivore defence: a large investment in quantitative defence compounds occurs at the expense of growth. We tested whether such a relationship also holds for growth rate and pathogen resistance. For 15 radish (Raphanus sativus L.) cultivars, we determined the potential growth rate and the resistance to fungal wilt disease caused by Fusarium oxysporum. We subsequently aimed to explain a putative negative relationship between growth rate and resistance based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…Significant differences in disease incidence between bacterized and non-bacterized plants were found from 17 days after inoculation onwards (Steijl et al, in preparation). The results are in agreement with those of a large number of independent experiments performed in our laboratory [25,26,30,31 ].…”
Section: Variation In Disease Incidencesupporting
confidence: 82%
See 2 more Smart Citations
“…Significant differences in disease incidence between bacterized and non-bacterized plants were found from 17 days after inoculation onwards (Steijl et al, in preparation). The results are in agreement with those of a large number of independent experiments performed in our laboratory [25,26,30,31 ].…”
Section: Variation In Disease Incidencesupporting
confidence: 82%
“…Healthy plants As indicated by previous PyMS analysis, slow-growing, resistant radish cultivars contained more cell wall material in the leaves but less in the roots when compared to faster-growing, more susceptible ones [25 ]. The within-variation of the group of root samples of untreated plants of cultivar SaxaiNova was not analysed separately.…”
Section: Carnationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest a negative relationship between  and plant tolerance to virus infection, as recently hypothesized to explain the difference in tolerance to fungi between genotypes of radish (Hoffland et al, 1996). A higher tolerance to virus for species and genotypes with low  could be the consequence of lower production and transport of photosynthates, inhibiting the multiplication and translocation of the virus.…”
Section: mentioning
confidence: 58%
“…One can also compare different genotypes under the same conditions to estimate whether the cost of defence is significant. Hoffland et al (1996) found that radish cultivars that were more protected against a fungus had to bear significant costs of more cell wall in leaves (but less wall and more protein in roots). Darrow & Bowers (1997) found no apparent cost (as decreased growth rate) for more potent defences, namely the iridioid glycosides, in Plantago species that were better protected against lepidopteran insects.…”
Section: Chemical Defencesmentioning
confidence: 99%